A siRNA system based on HSP70 promoter results in controllable and powerful gene silencing by heat‐induction. (7th August 2013) - Liao, Yi; Feng, Jianguo; Yi, Qian; Cui, Hanwei; He, Ling; Tang, Liling
Abstract : RNAi is a powerful tool for gene‐specific knockdown and gene therapy. However, the imprecise expression of siRNA limits the extensive application of RNAi in gene therapy. Here we report the development of a novel controllable siRNA expression vector pMHSP70psil that is initiated by HSP70 promoter. We determined the efficiency of the controllable siRNA system by targeting the gama‐synuclein (SNCG) gene in breast cancer cells MCF‐7. The results show that the controllable siRNA system can be induced to initiate siRNA expression by heat‐induction. The silencing effect of SNCG occurs at a relatively low level (10.1%) at 37°C, while it is significantly increased to 69.4% after heat induction at 43°C. The results also show that the controllable siRNA system inhibits proliferation of cancer cells by heat‐shock. Therefore, this RNAi strategy holds the promise of the high efficiency in gene knockdown at targeted times and locations, avoiding systemic side effects. It provides, for the first time, an approach to control siRNA expression by heat‐shock. © 2013 American Institute of Chemical Engineers Biotechnol. Prog ., 29:1289–1297, 2013